Sounding rocket SS-520 as a CubeSat launch vehicle. (May 2020) - Ito, T.; Yamamoto, T.; Nakamura, T.; Habu, H.; Ohtsuka, H.
Abstract: This paper investigates the launch capability of the SS-520 as a CubeSat launch vehicle. The SS-520 was developed by JAXA originally as a two-stage, spin-stabilized, solid-propellant sounding rocket. With less than 2.6 tons in total mass and 10 m in length, the SS-520-5 successfully launched a single 3U-sized CubeSat into orbit on February 3, 2018. The SS-520-5 obtained its capability as a CubeSat launch vehicle by installing a 3 rd stage solid motor in addition to the RCS between the 1 st and 2 nd stages. However, its launch capability was limited due to its rocket system configuration. In order to pursue the SS-520's launch capability, two effective modifications from the SS-520-5 are proposed: thrust enhancement of the 1 st stage motor and installation of an additional RCS between the 2 nd and 3 rd stages. The framework of launch capability analysis is established by a multi-objective genetic algorithm (MOGA), where its two objectives are selected as the altitudes of perigee and apogee. The analysis reveals that the two proposed modifications to the SS-520-5 work effectively but differently. The 10% increase of the 1 st stage enhancement is particularly effective when the target altitude of perigee is low (e.g., 200 km), whereas the installment of the additional RCS with 30 kg increases accessibility to a much higher altitude of perigee, even to circular orbit reaching altitudes of 550 km for a 1U-sized CubeSat and 280 km for a 6U-sized CubeSat. The simultaneous application of both modifications would result in launch capability able to deliver a 10-kg payload. From a more general perspective, the results in this paper suggest that it is possible for a very small launch vehicle (VSLV) of the 3-ton class and 10 m in length to deliver a 10-kg-class payload into low Earth orbit. Highlights: Two realistic modifications from the SS-520-5 are proposed as a CubeSat launcher. Thrust enhancement of the lower motor and additional RCS installation are effective. Each modification enables carrying a payload nearly twice as heavy. If both are applied simultaneously, it can deliver a 10-kg payload.